Combining the Elicitor Up-Regulated Production of Unusual Linear Diterpene-Derived Variants for an In-Depth Assessment of the Application Value and Risk of the Medicinal and Edible Basidiomycete Schizophyllum commune - Ying Wang; Fei Cao; Luning Zhou; Hanwei Liu; Hua Gao; Ge Cui; Changshan Niu; Peng Zhang; Dehai Li; Songqi Liu; Yan Jiang; Guangwei Wu (Molecules, 2024)
To better assess the practical value and avoid potential risks of the traditionally medicinal and edible basidiomycete Schizophyllum commune, which may arise from undescribed metabolites, a combination of elicitors was introduced for the first time to discover products from cryptic and low-expressed gene clusters under laboratory cultivation. Treating S. commune NJFU21 with the combination of five elicitors led to the upregulated production of a class of unusual linear diterpene-derived variants, including eleven new ones (1–11), along with three known ones (12–14). The structures and stereochemistry were determined by 1D and 2D NMR, HRESIMS, ECD, OR and VCD calculations. Notably, the elongation terminus of all the diterpenes was decorated by an unusual butenedioic acid moiety. Compound 1 was a rare monocyclic diterpene, while 2–6 possessed a tetrahydrofuran moiety. The truncated metabolites 4, 5 and 13 belong to the trinorditerpenes. All the diterpenes displayed approximately 70% scavenging of hydroxyl radicals at 50 μM and null cytotoxic activity at 10 μM. In addition, compound 1 exhibited potent antifungal activity against the plant pathogenic fungi Colletotrichum camelliae, with MIC values of 8 μg/mL. Our findings indicated that this class of diterpenes could provide valuable protectants for cosmetic ingredients and the lead compounds for agricultural fungicide development.